INVESTIGATING THE RELATIONSHIP BETWEEN ACCOUNTS RECEIVABLE, ACCOUNTS PAYABLE, INVENTORY, AND CASH MANAGEMENT ON THE PROFITABILITY OF MANUFACTURING COMPANIES IN TANZANIA - K, Kasahun (Economics and Statistics Research Journal (ESRJ), 2022)
This study examines the relationship between working capital management (WCM) and profitability of listed manufacturing companies (LMCs) in Tanzania. The study uses panel data approach and a finite distributed lag model to analyze financial reports of LMCs on the Dar es Salaam Stock Exchange from 2005 to 2018. The study found that WCM has a significant impact on the profitability of LMCs in Tanzania, with the current year marketing and administration expenses as moderators causing a lag of three years in the average collection period and each moderator to have a positive impact on profitability, while the current year average collection period had a negative impact on profitability. The study recommends that LMCs in Tanzania should consider the previous three years’ average collection period, administration expenses, marketing expenses, and effectiveness in managing working capital to enhance their profitability. The study contributes to literature by using the Dupont analysis to measure profitability and a finite distributed lag model to analyze the relationship between WCM and LMCs’ profitability